The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1002/chem.200390116
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of Transition Metal Carbonyl Cluster Anions: Structural Insights from Mass Spectrometry

Abstract: The anionic clusters [HOs(5)(CO)(15)](-), [PtRu(5)C(CO)(15)](2-), [Os(10)C(CO)(24)](2-), [Os(17)(CO)(36)](2-), [Os(20)(CO)(40)](3-), [Co(6)C(CO)(15)](2-), [Pt(3)Ru(10)C(2)(CO)(32)](2-) and [Pd(6)Ru(6)(CO)(24)](2-) have been analysed by energy-dependent electrospray ionisation mass spectrometry (EDESI-MS). Three main features have emerged. Firstly, carbonyl ligands are fragmented from clusters with compact metal cores in an orderly fashion, with each of the ions generated by CO loss having approximately equal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 81 publications
1
23
0
Order By: Relevance
“…The corresponding cluster k values of the fragment should be on the increase. Very interesting extensive work on the metal carbonyls that involves stripping off the CO ligands has been done by several research groups (Butcher, et al, 2002(Butcher, et al, , 2003Crawford, et al, 2006;Critchley, et al, 1999;Dyson, et al, 2001;Henderson, et al, 1998Henderson, et al, , 2009 Table 7). Although the series and the skeletal numbers predict that each of the Re skeletal atoms except one should have a hydrogen atom, the structural determination indicates all the hydrogen atoms are bridging (Miessler, et al, 2014) as observed in borane clusters.…”
Section: Limits Of the Carbonyl Cluster Seriesmentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding cluster k values of the fragment should be on the increase. Very interesting extensive work on the metal carbonyls that involves stripping off the CO ligands has been done by several research groups (Butcher, et al, 2002(Butcher, et al, , 2003Crawford, et al, 2006;Critchley, et al, 1999;Dyson, et al, 2001;Henderson, et al, 1998Henderson, et al, , 2009 Table 7). Although the series and the skeletal numbers predict that each of the Re skeletal atoms except one should have a hydrogen atom, the structural determination indicates all the hydrogen atoms are bridging (Miessler, et al, 2014) as observed in borane clusters.…”
Section: Limits Of the Carbonyl Cluster Seriesmentioning
confidence: 99%
“…These opposing processes are reflected in Tables 7 and 8. The removal of CO ligands from transition metal carbonyl clusters has been an intense field of research (Critchley, et al, 1999, Douglas, et al, 2001, Butcher, et al, 2002, 2003, Crawford, et al, 2006, Henderson, et al, 2009). The silicon clusters Si n (n=4-10) were theoretically studied (Slee, et al, 1989) (Hughes, et al, 2000).…”
Section: Capping and De-capping Seriesmentioning
confidence: 99%
“…An illustration is given in Table 6. Butcher, et al, 2003 DIFFERENCES BETWEEN THE 4n SERIES METHOD AND THE SEP METHOD…”
Section: Blackholes In the Nucleus And Ghost Skeletal Elementsmentioning
confidence: 99%
“…The analysis and categorization of stripping series of clusters may assist in improvement of understanding and appreciation of the work by Butcher and his research groups (Butcher, et al, 2003).…”
Section:  the Stripping Series Of Clustersmentioning
confidence: 99%
“…Transition-metal carbonyl cluster anions provide excellent electrospray ionization mass spectra (ESI-MS), and collision-induced dissociation (CID) can be used to selectively remove some or all of the CO ligands from the metal core [25]. We have used these properties in the past to study the reactivity of [CoRu 3 ]…”
mentioning
confidence: 99%